(untitled) (Filološke studije, 2019)
Following Castoriadis’ theory of social imaginary, as well as N. Frye’s and Riceour’s concept of narrative construction of society, the author shows a possibilty to use the notion of »founding myth« in the discussion of the Slovenian national identification. The founding myth is understood as a means of homogenisation which takes part in the process of constituting the social imaginary significations. The constitution of the founding myth is intertwined with material praxis and with the so called stock responses. The author shows some of the key mechanisms that have been involved in the formation of the Slovenian national identification, especially the feeling of endangerment and the bifocality of identification, which are both understood as stock responses. The 19th Century and the rise of jansenism were crucial in forming these stock responses, thus the author gives a brief description of the magazine Novice which has been established in 1848.